2018
DOI: 10.1371/journal.pone.0195336
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive value of the preoperative neutrophil-to-lymphocyte ratio for the development of hepatocellular carcinoma in HBV-associated cirrhotic patients after splenectomy

Abstract: The neutrophil to lymphocyte ratio (NLR), a simple marker of inflammation, has recently been showed to predict tumor recurrence in hepatocellular carcinoma (HCC) patients after hepatic resection or liver transplantation. However, whether it can be used to predict HCC development in cirrhotic patients remained unknown. The aim of this study was to evaluate the predictive value of the preoperative NLR for the development of HCC in cirrhotic patients who underwent splenectomy. A total of 230 HBV-associated cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…The mechanism by which the hematologic ratios in this study can be used to monitor the stages of HCC is unclear. Du et al [28] followed 230 patients with cirrhosis and found that preoperative NLR elevation was associated with an increased risk of progression to HCC in patients with cirrhosis. Jin et al [29] evaluated the prognostic value of NLR in 556 patients with HCC in BCLC stage A, and found that increased NLR was a poor prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which the hematologic ratios in this study can be used to monitor the stages of HCC is unclear. Du et al [28] followed 230 patients with cirrhosis and found that preoperative NLR elevation was associated with an increased risk of progression to HCC in patients with cirrhosis. Jin et al [29] evaluated the prognostic value of NLR in 556 patients with HCC in BCLC stage A, and found that increased NLR was a poor prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil‐to‐lymphocyte ratio (NLR) has been studied as a biomarker in multiple solid tumors, such as hepatocellular carcinoma, renal, breast, and metastatic melanoma . Several researchers have also investigated the NLR in ICC; however, little work has been done on the relative importance of the NLR, the platelet‐to‐lymphocyte ratio (PLR), and the systemic immune‐inflammation index (SII).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the variety of inflammations represent a useful prognostic marker for HCC, including fibrinogen, inflammation based index (IBI), C-reactive protein (CRP), inflammation based score (IBS), Glasgow prognostic score (GPS), and neutrophil to lymphocyte ratio (NLR) [14] . NLR is a simple marker of inflammation, it provides a good indication of the patient's overall inflammatory status, also it has been used to predict tumor recurrence in HCC patients after hepatic resection [15,16] hepatocellular carcinoma (HCC. NLR has been related with activate caspase-1, which induce to produce the interleukin-18 (IL-18) and interleukin-1β (IL-1β).…”
Section: Chronic Inflammationsmentioning
confidence: 99%
“…NLR is interested in NF-κB and MAPK for signalling pathways. Thus, NLRs share in progression of HCC [15,16] .…”
Section: Chronic Inflammationsmentioning
confidence: 99%